2018
DOI: 10.1177/1932296818789175
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement Pathways for New Diabetes Technologies in Europe: Top-Down Versus Bottom-Up

Abstract: Reimbursement by payers (policy makers and budget holders) is critical for the uptake and use of new diabetes technologies. The purpose of this article is to describe the different reimbursement pathways that exist for new diabetes technologies in five selected European countries using examples of recent reimbursement decisions. Countries can be grouped into one of three categories: "top-down" (where reimbursement decisions are usually made by policy makers, eg, France), "bottom-up" (where reimbursement decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…There are mixed results from studies regarding cost-effectiveness depending on the setting, the healthcare structure, the endpoints and methodology used. 19,4649 However, several studies have shown reduced incremental cost-effectiveness per quality-adjusted life year (QALY) gained at different HbA1c thresholds. Results for all HbA1c thresholds were below the willingness-to-pay threshold of US$100 per QALY for people living with diabetes.…”
Section: Solutions Offered By Diabetes Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are mixed results from studies regarding cost-effectiveness depending on the setting, the healthcare structure, the endpoints and methodology used. 19,4649 However, several studies have shown reduced incremental cost-effectiveness per quality-adjusted life year (QALY) gained at different HbA1c thresholds. Results for all HbA1c thresholds were below the willingness-to-pay threshold of US$100 per QALY for people living with diabetes.…”
Section: Solutions Offered By Diabetes Technologiesmentioning
confidence: 99%
“…However, very different approaches and rates of coverage have been achieved depending on the country's healthcare system structure and resources. 16,17 Large transatlantic registry comparisons have shown differences in metabolic outcomes, in spite of similar population characteristics, partly in relation to the different frequencies of use of diabetes technologies. 18 Cost-effectiveness of diabetes technologies has also shown differences depending on the type of technology, setting, healthcare system structure and the endpoints considered.…”
Section: Patient and Clinician Perspectives On The Use Of Diabetes Technologiesmentioning
confidence: 99%
“…They are interested in clinical and cost‐effectiveness; however, budget holders are mostly interested if new technology can help them achieve their budget targets. Most regions expect manufacturers to generate short‐term real‐world evidence for new technologies with a significant budget impact 70 …”
Section: Insulin Pump Treatment In T2dmentioning
confidence: 99%
“…Nevertheless, in most countries, it is unlikely that a new diabetes technology will reach widespread use without being reimbursed/funded by payers. 70 As the ultimate decision makers on reimbursement, the payers/ budget holders need to make a comprehensive assessment of several factors, such as clinical efficacy, safety and effectiveness (clinical evidence), along with the direct and indirect costs and quality-of-life (QoL) improvements (economics/humanistic evidence), in order to determine the coverage and funding for a new medical technology. 71 For any new treatment to be reimbursed, these key value drivers of payers need to be properly addressed.…”
Section: Meeting the Needs Of Payersmentioning
confidence: 99%
See 1 more Smart Citation